11p15.4 Microdeletion Associates with Hemihypertrophy - Surasak Puvabanditsin; Mehrin Sadiq; Marianne Jacob; Maaz Jalil; Kenya Cabrera; Omer Choudry; Rajeev Mehta (Case Reports in Genetics)
We report a preterm female infant with intrauterine growth retardation, dysmorphic facies, missing rib, small hands and feet, and hemihypertrophy. The results of whole genome SNP microarray analysis showed approximately 77 Kb interstitial deletion of the short arm of chromosome 11 (11p15.4). We report novel clinical findings of this rare genetic condition.